polyester film
Patent Information
- Application Number
- CN202580022078.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-21
- Filing Date
- 2025-03-21
- Publication Date
- 2026-10-20
AI Technical Summary
然而,聚酯薄膜与亲水性粘接剂的粘接性并不充分,特别是在通过拉伸处理而具有取向性的聚酯薄膜的情况下,其倾向变得更为显著
[0055]本发明的易粘接性聚酯薄膜通过提高涂布层的柔软性并保持与润滑剂颗粒的高密合性,能够防止涂布层中的颗粒的脱落,防止脱落颗粒对接触面的损伤。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention provides an easy-to-adhere polyester film that will not cause damage to the opposite side of the coating layer or the functional layer formed on the opposite side during post-processing such as film formation and functional layer application, and a laminated polyester film having the functional layer. Background Technology
[0002] Hard-coated films with a transparent hard coating are used on the front surfaces of touch panels, displays for computers, televisions, liquid crystal displays, and decorative materials. Furthermore, panel components used in displays are formed by bonding the hard-coated film to a polarizer or to other components, but in this bonding process, an adhesive component is applied before bonding.
[0003] Transparent plastic films used as substrates are typically transparent polyester films. To improve the adhesion between the polyester film substrate and the hard coating and adhesive, an easily adhesive coating layer is usually applied to the surface of the polyester film as an intermediate layer.
[0004] The aforementioned hard-coated films require durability against temperature, humidity, and light, as well as transparency, chemical resistance, scratch resistance, and stain resistance. Furthermore, since they are often used on the surfaces of displays and decorative materials, visual legibility and design flexibility are also required. Therefore, to suppress glare and iridescent spots caused by reflected light when viewed from any angle, a multi-layered anti-reflective layer, consisting of stacked high-refractive-index and low-refractive-index layers, is typically applied over the hard coating.
[0005] In recent years, hard coatings with various compositions have been developed, and the adhesion between the substrate and the hard coating is discussed based on their composition. For example, when using a film with a hard coating laminated on it in a liquid crystal television display, in order to ensure high reliability for long-term use, not only the initial adhesion immediately after lamination is required, but also properties such as resistance to damp heat and retention of adhesion over time are also required.
[0006] For the aforementioned adhesives, similar requirements exist regarding durability against temperature, humidity, and light, transparency, chemical resistance, scratch resistance, and stain resistance. Furthermore, since they are frequently used on the surfaces of displays and decorative materials, visual legibility and design flexibility are also essential. In recent years, adhesives with various compositions have been developed, and the adhesion between the substrate and the adhesive is discussed based on their composition. For example, when components bonded using adhesives are used in the displays of LCD televisions, to ensure high reliability for long-term use, not only initial adhesion after lamination is required, but also resistance to damp heat and moisture, and retention of adhesion over time.
[0007] In liquid crystal display devices, polarizing plates are disposed on both sides of the glass substrate on which the surface of the liquid crystal panel is formed, depending on the image formation method. The polarizing plates typically have a structure in which a protective polarizing film is bonded to both sides of a polarizer made of a polyvinyl alcohol-based film and a dichroic material such as iodine via a hydrophilic adhesive such as a polyvinyl alcohol-based resin. From the viewpoint of optical properties and transparency, triacetyl cellulose film has traditionally been used as the protective film for protecting the polarizer.
[0008] However, the durability of triacetylcellulose is not sufficient. When using a polarizing plate with a triacetylcellulose film as a protective film for polarizers under high temperature or high humidity conditions, the polarization degree, hue, and other performance characteristics of the polarizer may sometimes decrease. Furthermore, in recent years, to meet the demand for thinner displays, there is a requirement for thinner polarizing plates; however, from the viewpoint of maintaining moisture barrier properties, there are limits to the thinning of triacetylcellulose films. Therefore, a solution using polyester film has been proposed as a protective film for polarizers that possesses both durability and moisture barrier properties (for example, see Patent Document 1).
[0009] Triacetyl cellulose film used as a protective film for polarizers undergoes alkali treatment on its surface, resulting in extremely high affinity for hydrophilic adhesives. Therefore, the protective film composed of triacetyl cellulose film exhibits extremely high adhesion to polarizers coated with hydrophilic adhesives. However, the adhesion between polyester film and hydrophilic adhesives is not sufficient, especially in the case of polyester films that have been oriented through stretching treatment, where this tendency becomes more pronounced. Therefore, to improve adhesion to polarizers or hydrophilic adhesives coated on polarizers, it has been reported to form a covering layer by coating the surface of the polyester film with a highly hydrophilic material (see, for example, Patent Document 1).
[0010] In the field of readily adhesive polyester films, it has been reported that laminated polyester films, in which a coating layer containing a polyester resin containing a naphthalene dicarboxylic acid component is provided on at least one side of the polyester film, exhibit excellent adhesion to surface functional layers such as hard coatings (for example, see Patent Document 2).
[0011] In addition, it has been reported that an easy-to-adhere polyester film with a coating layer provided on at least one side of the polyester film exhibits excellent adhesion to an optical functional layer under high temperature and high humidity, wherein the coating layer contains a polyurethane resin with aliphatic polycarbonate polyol as a component, which has excellent flexibility and high adhesion (for example, see Patent Document 3).
[0012] Existing technical documents
[0013] Patent documents
[0014] Patent Document 1: Japanese Patent Application Publication No. 2013-063610
[0015] Patent Document 2: Japanese Patent Application Publication No. 2011-246663
[0016] Patent Document 3: Japanese Patent Application Publication No. 2011-168053 Summary of the Invention
[0017] The problem the invention aims to solve
[0018] In recent years, high-quality films with excellent transparency and no damage have been particularly sought after in applications involving near-surface parts, such as display components. Furthermore, there is a trend towards increasing film transport speeds as a process condition to improve productivity, requiring films that do not suffer damage even under more demanding conditions. In display applications, multiple surface processing steps are typically involved, but post-processing can lead to reduced productivity due to damage.
[0019] The inventors of this invention have made this invention with regard to the generation of damage, for example, that may be associated with adhesive or slip-resistant layers, in polyester films having a polyester film substrate and a coating layer.
[0020] This invention was made against the backdrop of the aforementioned problems in the prior art. Specifically, the object of this invention is to provide an easily bondable polyester film that, during post-processing such as film formation and functional layer application, can suppress damage to the opposite side of the coating layer during winding, and also suppresses damage to the functional layer formed on the opposite side. Furthermore, a laminated polyester film having this functional layer is provided.
[0021] To achieve this objective, the inventors conducted in-depth research and discovered that by controlling the softness of the coating layer, the shedding of particles contained in the coating layer can be suppressed, making it less prone to damage, thus completing this invention. Specifically, this invention comprises the following technical solution.
[0022] Solution for solving the problem [1]
[0024] An easy-to-adhere polyester film, comprising an easy-to-adhere polyester film substrate and a coating layer.
[0025] The coating layer is formed from a composition comprising polycarbonate polyurethane resin (A), polyester resin (B), end-capped isocyanate crosslinking agent (C), and particles.
[0026] In the particle shedding test, the amount of particles shed within the field of view is less than 30%. [2]
[0028] According to the easy-to-adhere polyester film described in [1], the difference in film haze before and after the particle shedding test is less than 0.55%. [3]
[0030] According to the easy-to-adhere polyester film described in [1] or [2], wherein the polycarbonate polyurethane resin (A) has the structure shown in formula (1) in the molecule.
[0031]
[0032] (In the formula, * represents the bonding site, and n represents an integer from 5 to 10.) [4]
[0034] The easy-to-adhere polyester film according to any one of [1] to [3], wherein the polyester resin (B) is a polyester resin having the structure shown in formula (1) in its molecule.
[0035]
[0036] (In the formula, * represents the bonding site, and n represents an integer from 5 to 10.) [5]
[0038] A method for manufacturing an easy-to-adhere polyester film, comprising the following steps:
[0039] The process of coating a composition for forming a coating layer onto at least one side of a polyester film substrate.
[0040] The composition for forming the coating layer comprises polycarbonate polyurethane resin (A), polyester resin (B), end-capped isocyanate crosslinking agent (C), and particles.
[0041] The polycarbonate polyurethane resin (A) has the structure shown in formula (1) in its molecule.
[0042]
[0043] (In the formula, * represents the bonding site, and n represents an integer from 5 to 10.)
[0044] The polyester resin (B) has the structure shown in formula (1) in its molecule.
[0045]
[0046] (In the formula, * represents the bonding site, and n represents an integer from 5 to 10.)
[0047] The terminated isocyanate crosslinking agent (C) has the structure shown in formula (1) in the molecule.
[0048]
[0049] (In the formula, * represents the bonding site, and n represents an integer from 5 to 10.) [6]
[0051] A laminated polyester film, wherein a functional layer is further provided on the coating layer of the easy-to-adhere polyester film as described in any one of [1] to [4]. [7]
[0053] A method for manufacturing a laminated polyester film, comprising the method of manufacturing the laminated polyester film described in [6], comprising the step of coating a functional layer forming composition on the coating layer of the easy-to-adhere polyester film described in any one of [1] to [4].
[0054] The effects of the invention
[0055] The easy-to-adhere polyester film of the present invention can prevent particles in the coating layer from falling off and prevent damage to the contact surface by improving the flexibility of the coating layer and maintaining high adhesion with lubricant particles.
[0056] Therefore, during post-processing such as film formation and functional layer application of the coated film, and during winding into a roll, damage to the opposite side of the coated layer can be suppressed. Furthermore, damage to the functional layer formed on the opposite side can also be suppressed. In addition, due to its excellent anti-blocking and transparency properties, it can be widely used in optical applications, etc. Detailed Implementation
[0057] Polyester film substrate
[0058] The polyester film used as the substrate in the easily adhesive polyester film of the present invention is a film mainly composed of polyester resin. Here, "film mainly composed of polyester resin" means a film formed from a resin composition containing 50% by mass or more of polyester resin. When blended with other polymers (e.g., polycarbonate resin, polyimide resin, etc.), it means containing 50% by mass or more of polyester resin; when copolymerized with other monomers, it means containing 50% by mole or more of polyester structural units. Preferably, the polyester film contains 90% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass of polyester resin.
[0059] There are no particular limitations on the materials of polyester resins; copolymers formed by the condensation of dicarboxylic acid components and diol components, or mixtures thereof, can be used.
[0060] Examples of dicarboxylic acid components that constitute polyester resins include terephthalic acid, isophthalic acid, phthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracene dicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyl adipic acid, trimethyl adipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, octanoic acid, and dodecanedicarboxylic acid.
[0061] Examples of diols that constitute polyester resins include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, decamethyldiol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.
[0062] One or more dicarboxylic acid components and two diol components can be used. In addition, other polycarboxylic acid components such as trimellitic acid and other polyol components such as trimethylolpropane can also be added appropriately.
[0063] Specifically, examples of polyester resins include polyethylene terephthalate, polyethylene terephthalate, polyethylene terephthalate, and polyethylene naphthalate. Among these, polyethylene terephthalate is preferred from the perspective of balancing physical properties and cost. Furthermore, including other copolymer components and other polymers is also a preferred approach to control optical properties such as polarization. From the viewpoint of controlling the optical properties of the polyester film, preferred copolymer components include diethylene glycol and copolymer components with norbornene side chains.
[0064] The intrinsic viscosity of the polyester resin (solvent: phenol / tetrachloroethane = 60:40) is, for example, 0.50~1.0 dl / g.
[0065] To improve the handling properties of polyester films, such as slippage and winding, the films can contain inactive particles. Examples of inactive particles include inorganic particles such as silica, kaolinite, talc, light calcium carbonate, heavy calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, zinc sulfate, zinc carbonate, titanium dioxide, satin white, aluminum silicate, diatomaceous earth, calcium silicate, aluminum hydroxide, hydrated halloysite, magnesium carbonate, and magnesium hydroxide, as well as organic particles such as melamine, acrylics, styrene, and silicone. The average particle size was determined using the method described in the examples (average particle size based on the number of SEM samples).
[0066] To maintain high transparency, it is preferable that the content of inactive particles in the film is as low as possible. Therefore, it is preferable to form a multilayer structure in which particles are present only on the surface of the film, or to have no particles in the film at all, with particles present only in at least one side of the coating layer laminated on the polyester film.
[0067] It should be noted that "substantially free of particles" means, for example, in the case of inorganic particles, that when quantitative analysis of elements derived from particles is performed by fluorescence X-ray analysis, the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit. This is because, even without actively adding particles to the substrate film, contaminants from foreign matter, raw material resins, or dirt adhering to the production line or equipment during the film manufacturing process can inevitably be mixed into the film.
[0068] Furthermore, when the polyester film is made into a multilayer structure, two three-layer structures can be produced, in which the inner layer substantially does not contain inactive particles, and only the outermost layer (second layer) contains inactive particles. This allows for a balance between transparency and processability, and is therefore preferred.
[0069] The polyester film used as the substrate can be a single layer or composed of two or more layers laminated together. Furthermore, various additives can be included in the film as needed, provided they are within the scope of achieving the effects of this invention. Examples of additives include antioxidants, lightfastness agents, anti-gelling agents, organic wetting agents, antistatic agents, ultraviolet absorbers, and surfactants. When the film has a laminated structure, it is preferable to include additives according to the function of each layer. For example, adding ultraviolet absorbers to the inner layers to prevent light degradation of the polarizer is also a preferred approach.
[0070] Polyester film can be manufactured using conventional methods. For example, it can be obtained by melting and extruding a material containing the aforementioned polyester resin into a film shape and then cooling and solidifying it using a casting drum. As the polyester film of the present invention, either unstretched film or stretched film can be used, but stretched film is preferred from the perspective of durability, such as mechanical strength and chemical resistance.
[0071] When the polyester film is a stretched film, the stretching method is not particularly limited, and can include longitudinal uniaxial stretching, transverse uniaxial stretching, longitudinal and transverse successive biaxial stretching, and simultaneous longitudinal and transverse biaxial stretching. When stretching a polyester film, stretching can be performed before or after the lamination of the easily bondable coating layer (described later). Alternatively, uniaxial stretching can be performed longitudinally or transversely before laminating the easily bondable coating layer, and then stretched in the other direction after laminating the coating layer.
[0072] Coating layer
[0073] The easy-to-adhesive polyester film of the present invention comprises a polyester film and a coating layer. For example, an easy-to-adhesive coating layer is laminated on at least one side of a polyester film serving as a substrate. In the present invention, the coating layer is a layer formed from a composition comprising a polycarbonate polyurethane resin (A), a polyester resin (B), a capped isocyanate crosslinking agent (C), and particles. The easy-to-adhesive polyester film of the present invention can be manufactured by a process of coating a composition for forming a coating layer onto at least one side of a polyester film substrate.
[0074] The present invention can also have the coating layer of the present invention on both sides of the polyester film substrate.
[0075] The following is a detailed description of each component of the coating layer. The adhesive resin constituting the coating layer is a resin with easy adhesion, including polycarbonate polyurethane resin (A) and polyester resin (B) which are urethane resins having a polycarbonate structure, and the crosslinking agent includes a capped isocyanate-based crosslinking agent (C).
[0076] Polycarbonate polyurethane resin (A) contains a cyclohexane ring structure in its molecule, and has a structure in which at least one (especially one or two) hydrogen atoms on the cyclohexane ring are replaced by a hydrocarbon group (hereinafter, this structure is sometimes referred to as the "cyclohexane ring structure"). In other words, it has a structure in which at least one hydrogen atom on the cyclohexane ring is bonded to a carbon atom of a hydrocarbon group (e.g., an alkyl group having 1 to 3 carbon atoms, an alkylene group having 1 to 3 carbon atoms, etc.).
[0077] The polycarbonate polyurethane resin (A) also has a structure in which a methylene chain containing 5 or more but less than 10 carbon atoms is included in its molecule (hereinafter, this structure is sometimes referred to as "C5~C10 methylene chain structure"). The polycarbonate polyurethane resin (A) can be one or a mixture of two or more.
[0078] Considering the interaction with the polycarbonate polyurethane resin (A), the polyester resin (B) has a cyclohexane ring structure and / or a C5-C10 methylene chain structure in its molecule. That is, it has either a cyclohexane ring structure or a C5-C10 methylene chain structure in its molecule. The polyester resin (B) can be one or a mixture of two or more.
[0079] Considering the interaction with polycarbonate polyurethane resin (A) and polyester resin (B), the end-capped isocyanate crosslinking agent (C) has a cyclohexane ring structure and / or a C5-C10 methylene chain structure in its molecule. That is, it has both or either a cyclohexane ring structure and a C5-C10 methylene chain structure in its molecule. The end-capped isocyanate crosslinking agent can be one or a mixture of two or more.
[0080] In one manner, the polycarbonate polyurethane resin (A) has the structure shown in formula (1) in the molecule;
[0081]
[0082] (In the formula, * represents the bonding site, and n represents an integer from 5 to 10.)
[0083] By giving the polycarbonate polyurethane resin (A) the above-described structure, the flexibility of the coating layer can be improved, thereby maintaining high adhesion to particles (e.g., lubricant particles). Furthermore, it prevents particles from detaching from the coating layer and avoids damage to the contact surface from detached particles.
[0084] In one manner, the polyester resin (B) has the structure shown in formula (1) in the molecule.
[0085]
[0086] (In the formula, * represents the bonding site, and n represents an integer from 5 to 10.)
[0087] By giving the polyester resin (B) the above-described structure, the flexibility of the coating layer can be improved, thereby maintaining high adhesion to particles (e.g., lubricant particles). Furthermore, it prevents particles from detaching from the coating layer and avoids damage to the contact surface from detached particles.
[0088] Furthermore, in this invention, good compatibility with polycarbonate polyurethane resin (A) is maintained, and the adhesion between the substrate and the coating layer is improved. While not to be limited by any specific theory, it is speculated that a moderate interaction (stereostructure) is formed between the polycarbonate polyurethane resin (A) and the polyester resin (B), which simultaneously satisfies particle retention and flexibility.
[0089] In one manner, the isocyanate-based crosslinking agent (C) has the structure shown in formula (1) in the molecule;
[0090]
[0091] (In the formula, * represents the bonding site, and n represents an integer from 5 to 10.)
[0092] The isocyanate-based crosslinking agent (C) maintains good compatibility with polycarbonate polyurethane resin (A) and polyester resin (B) by having the structure shown in formula (1) in its molecule. It is speculated that due to the good compatibility, the isocyanate-based crosslinking agent (C) can achieve the effect of uniform crosslinking in the resin and forming a stronger coating film.
[0093] The "cyclohexane ring structure" contained in the molecules of the polycarbonate polyurethane resin (A), polyester resin (B), and the end-capped isocyanate crosslinking agent (C) mentioned above can be exemplified by the structure shown in formula (1).
[0094]
[0095] (In the formula, * indicates the bonding site.)
[0096] As shown in formula (1), the structure shown in formula (1a) is preferred.
[0097]
[0098] (In the formula, * is the same as above.)
[0099] Furthermore, the structure shown in equation (1b) is more preferred.
[0100]
[0101] (In the formula, * is the same as above.)
[0102] The structure shown in formula (1b) above is more preferably derived from cyclohexanediethanol (especially 1,4-cyclohexanediethanol). In this case, the two asterisks become sites for bonding with the oxygen atoms constituting the resin.
[0103] In addition, as a “C5~C10 methylene chain structure”, the structure shown in formula (2) can be cited as an example.
[0104]
[0105] (In the formula, n represents an integer from 5 to 10, and * represents the bonding site.)
[0106] In formulas (1) and (2) above, * represents the site where it is bonded to an atom constituting the adhesive resin or crosslinking agent. Examples of this atom, whether the atom is the same or different, include hydrogen atoms, carbon atoms, oxygen atoms, nitrogen atoms, etc. Preferably, at least one of the two * in each formula is a carbon atom, oxygen atom, nitrogen atom, etc.
[0107] In the above formula (2), n is preferably 5 to 9, and more preferably 5 to 6.
[0108] The "cyclohexane ring structure" and "C5~C10 methylene chain structure" contained in the polycarbonate polyurethane resin (A), polyester resin (B) and the end-capped isocyanate crosslinking agent (C) may be the same or different.
[0109] By employing a coating layer formed from an adhesive resin and a crosslinking agent having such a structure, the adhesion between the polyester film substrate and the functional layer is significantly improved.
[0110] The reason for this is the good compatibility between the coating layer and the functional layer described later. Furthermore, the functional layer, obtained by UV curing under UV irradiation, has a cross-linked mesh structure. The polycarbonate polyurethane resin (A), polyester resin (B), and end-capped isocyanate crosslinking agent (C) of the coating layer all have at least a cyclohexane ring structure or a C5-C10 methylene chain structure in their molecules, thus the resins interact with each other, easily fusing and entangled. Moreover, it is believed that by entangled these intertwined resins with the mesh structure of the functional layer formed thereon, a coating layer with superior adhesion compared to previous methods is achieved. Furthermore, since the coating layer contains polyester resin (B), its adhesion to the polyester film as the substrate also becomes good, resulting in a coating layer with even superior adhesion.
[0111] (Polycarbonate polyurethane resin (A))
[0112] The polycarbonate polyurethane resin (A) may have the following two structures in its molecule: a cyclohexane ring structure, that is, a structure in which a cyclohexane ring structure is contained in its molecule and at least one hydrogen atom on the cyclohexane ring is replaced by a hydrocarbon group; and a C5~C10 methylene chain structure, that is, a structure containing a methylene chain with 5 or more carbon atoms and less than 10 carbon atoms.
[0113] The content of cyclohexane ring structures in the polycarbonate polyurethane resin (A) is typically 5% by mass or more and 55% by mass or less, preferably 10% by mass or more and 50% by mass or less, and more preferably 15% by mass or more and 45% by mass or less. If the content is 5% by mass or more, a sufficient number of cyclohexane ring structure units interacting with each other exist, thus maintaining the strength of the resin in the coating layer and facilitating good particle release. If the content is 55% by mass or less, the resin in the coating layer tends to maintain its flexibility, thereby strengthening particle retention and optimizing particle release.
[0114] The content of cyclohexane ring structure in polycarbonate polyurethane resin (A) is calculated based on the cyclohexane ring structure (-C6H). 10 The value is obtained by measuring the mass of -CH2- relative to 100g of the total mass of polycarbonate polyurethane resin (A). Specifically, it can be calculated from "the molecular weight and molar percentage of each component constituting polycarbonate polyurethane resin (A), such as polycarbonate diol and diisocyanate", "the molar percentage of the component with a cyclohexane ring", and "the proportion of the molecular weight of the cyclohexane ring structure among the molecular weights of the component with a cyclohexane ring".
[0115] The content of C5-C10 methylene chain structures in the polycarbonate polyurethane resin (A) is typically 5% by mass or more and 55% by mass or less, preferably 10% by mass or more and 50% by mass or less, and more preferably 15% by mass or more and 45% by mass or less. If the content is 5% by mass or more, a sufficient number of C5-C10 methylene chain structure units interacting with each other are present, thus increasing the resin entanglement in the coating layer, maintaining strength, and easily achieving good adhesion under high temperature and humidity. If the content is 55% by mass or less, the resin flexibility of the coating layer is maintained, and particle shedding is also easily achieved.
[0116] The content of C5-C10 methylene chain structures in polycarbonate polyurethane resin (A) is calculated based on the C5-C10 methylene chain structure (-(CH2)). n The value obtained is the ratio of the mass of (-, n as above) to 100g of the total mass of polycarbonate polyurethane resin (A). Specifically, it can be calculated from "the molecular weight and molar percentage of each component constituting polycarbonate polyurethane resin (A), such as polycarbonate diol and diisocyanate", "the molar percentage of the component having methylene chains with 5 or more carbon atoms and 10 or less", and "the proportion of the molecular weight of the methylene chains with 5 or more carbon atoms and 10 or less among the molecular weights of the components having methylene chains with 5 or more carbon atoms and 10 or less".
[0117] The polycarbonate polyurethane resin (A) is obtained by adding polycarbonate diol, diisocyanate, and diol as a chain extender as needed, wherein at least one component contains a cyclohexane ring structure and / or a C5-C10 methylene chain structure, and the polycarbonate polyurethane resin (A) as a whole contains both the cyclohexane ring structure and the C5-C10 methylene chain structure.
[0118] The polycarbonate diol component required for preparing polycarbonate polyurethane resin (A) can be produced by reacting the diol component with the carbonate component.
[0119] Examples of diol components include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, 1,4-cyclohexanediethanol, decamethyldiol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone. Among these, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, and 1,4-cyclohexanediethanol, which possess the aforementioned cyclohexane ring structure, are particularly preferred.
[0120] Furthermore, hexamethylenediol, decamethylenediol, 1,5-pentanediol, 1,6-hexanediol, etc., having the above-mentioned C5~C10 methylene chain structure, are particularly preferred.
[0121] Furthermore, these diol components can be used alone or in combination of two or more. There is no particular limitation on the ratio when combining two or more components; it can be adjusted to obtain a polycarbonate polyurethane resin that achieves the desired properties.
[0122] Examples of carbonate components include dimethyl carbonate, ethylene carbonate, and carbonate chloride.
[0123] Examples of diisocyanate components required for preparing polycarbonate polyurethane resin (A) include toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4-methylene dicyclohexyl diisocyanate, 1,2-bis(isocyanate methyl)cyclohexane, and 1,4-bis(isocyanate methyl)cyclohexane. Among these, isophorone diisocyanate, 4,4-methylene dicyclohexyl diisocyanate, 1,2-bis(isocyanate methyl)cyclohexane, and 1,4-bis(isocyanate methyl)cyclohexane having the aforementioned cyclohexane ring structure are particularly preferred. Furthermore, these isocyanate components can be used alone or in combination of two or more. The ratio when combining two or more is not particularly limited and can be adjusted to obtain a polycarbonate polyurethane resin with the desired properties.
[0124] (Polyester resin (B))
[0125] Regarding the polyester resin (B) used in conjunction with polycarbonate polyurethane resin (A), its molecule may have a cyclohexane ring structure and / or a C5~C10 methylene chain structure.
[0126] The content of the cyclohexane ring structure in the polyester resin (B) is generally more preferably 5% by mass or more and 20% by mass or less, and more preferably 10% by mass or more and 15% by mass or less. By setting the content to 20% by mass or less, it is easy to ensure the fluidity and flexibility of the resin. By setting it to 5% by mass or more, it is possible to ensure the number of cyclohexane ring structure units that interact with the polycarbonate polyurethane resin (A), thereby ensuring the strength of the resin in the coating layer and making it easier to remove particles.
[0127] The content of cyclohexane ring structure in polyester resin (B) is calculated based on the cyclohexane ring structure (-C6H). 10 The value is obtained by measuring the mass of -CH2- relative to 100g of the total mass of polyester resin (B). Specifically, it can be calculated from "the molar percentage and molecular weight of each monomer component constituting the polyester resin (B)," "the molar percentage of monomer components containing a cyclohexane ring among all monomer components," and "the proportion of the molecular weight of the monomer components containing a cyclohexane ring in the molecular weight of the monomer components containing a cyclohexane ring."
[0128] The content of C5-C10 methylene chain structures in the polyester resin (B) is generally more preferably 5% by mass or more and 20% by mass or less, and more preferably 10% by mass or more and 15% by mass or less. By setting the content to 20% by mass or less, it is easy to ensure the fluidity and flexibility of the resin. By setting it to 5% by mass or more, it is possible to ensure the number of units of the C5-C10 methylene chain structures that interact with the polycarbonate polyurethane resin (A), thereby ensuring the strength of the resin in the coating layer and making it easier to remove particles.
[0129] The content of C5~C10 methylene chain structures in polyester resin (B) is calculated based on the C5~C10 methylene chain structure (-(CH2)). n The value obtained by comparing the mass of (-, n as above) with the total mass of polyester resin (B) of 100g. Specifically, it can be calculated from "the molar percentage and molecular weight of each monomer component constituting the polyester resin (B)," "the molar percentage of monomer components having methylene chains with 5 or more carbon atoms and less than 10 carbon atoms among all monomer components," and "the proportion of the molecular weight of methylene chains with 5 or more carbon atoms and less than 10 carbon atoms among the molecular weight of monomer components having methylene chains with 5 or more carbon atoms and less than 10 carbon atoms."
[0130] Polyester resin (B) is obtained by polycondensation of a dicarboxylic acid component and a diol component, and is a copolyester formed by the dicarboxylic acid component and the diol component. One or more dicarboxylic acid components and diol components may be used. In this invention, at least one of the dicarboxylic acid component and diol component has a cyclohexane ring structure and / or a C5-C10 methylene chain structure.
[0131] Examples of dicarboxylic acid components include terephthalic acid, isophthalic acid, phthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracene dicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, cyclohexylmethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, cyclohexylmethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyl adipic acid, trimethyl adipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, octanoic acid, dodecanedicarboxylic acid, and 1,1-cyclohexanediacetic acid. Among them, cyclohexylmethylmalonic acid, cyclohexylmethylsuccinic acid, and 1,1-cyclohexanediacetic acid have the above-mentioned cyclohexane ring structure, and are particularly preferred.
[0132] Water dispersibility can be imparted to polyester resin (B) by copolymerizing, for example, dicarboxylic acid components with hydrophilic groups (such as sulfonyl groups), in addition to the dicarboxylic acid components mentioned above. Examples of dicarboxylic acid components with hydrophilic groups include 5-sulfoterephthalic acid, 5-sulfoisophthalic acid, and their salts. This dicarboxylic acid component with hydrophilic groups can be copolymerized in the range of 1 to 10 mol% of all dicarboxylic acid components.
[0133] As long as the quantity is small, cyclohexylacetic acid, etc., which are monocarboxylic acids, can also be used as needed.
[0134] Examples of diol components include ethylene glycol, propylene glycol, neopentyl glycol, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, 1,4-cyclohexanediethanol, hexamethylene glycol, decamethyl glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone. Among these, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, and 1,4-cyclohexanediethanol, which possess the aforementioned cyclohexane ring structure, are particularly preferred.
[0135] In addition, hexamethylenediol, decamethylenediol, 1,5-pentanediol, 1,6-hexanediol, etc., which have the above-mentioned C5~C10 methylene chain structure, are particularly preferred.
[0136] The ratio of the dicarboxylic acid component to the diol component is not particularly limited and can be adjusted in a way that yields a polyester with the desired properties.
[0137] In this invention, the adhesive resin comprises polycarbonate polyurethane resin (A) and polyester resin (B). The ratio of the two is not particularly limited as long as it ensures the physical properties of the resulting coating layer. When the total amount of the adhesive resin is set to 100% by mass, the polycarbonate polyurethane resin (A) is generally preferably 35% by mass or more and 85% by mass or less, more preferably 40% by mass or more and 80% by mass or less, and even more preferably 45% by mass or more and 75% by mass or less. By making the polycarbonate polyurethane resin (A) 35% by mass or more, a balance between the softness and hardness of the urethane resin can be ensured, thus ensuring adhesion over time. Furthermore, by setting it to 85% by mass or less, a balance between the hardness and softness of the coating layer can be maintained, and softness can also be improved, thus optimally functioning as a coating layer.
[0138] (Cross-linking agent)
[0139] In this invention, a crosslinking agent is included in the composition used to form the coating layer in order to form a crosslinked structure between the resins in the coating layer. By including the crosslinking agent, the adhesion under high temperature and high humidity conditions can be further improved. Furthermore, it is believed that by including the crosslinking agent together with the polycarbonate polyurethane resin (A) and the polyester resin (B), the flexibility of the coating layer can be appropriately adjusted, thus improving particle shedding resistance. As a specific crosslinking agent, isocyanate-based crosslinking agents (especially the end-capped isocyanate-based crosslinking agent (C) described later) can be cited from the viewpoint of maintaining the stability of the coating solution over time and the flexibility of the coating layer. In addition, catalysts or the like can be used appropriately as needed to promote the crosslinking reaction.
[0140] The preferred crosslinking agent is a polyisocyanate-based crosslinking agent with at least two functions (and more specifically, at least three functions). Examples of such crosslinking agents include urea-formate bodies, biuret bodies, adducts, urea-diketone bodies, and isocyanurate bodies of polyisocyanate (especially diisocyanate) compounds. Examples of polyisocyanate compounds include hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, cyclohexane-1,2-dimethylbis(methylene)diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, and bis(isocyanate-methyl)cyclohexane.
[0141] Among the above-mentioned polyisocyanate crosslinking agents, one or more polyisocyanate crosslinking agents selected from the group consisting of urea formate, biuret and adducts have low steric hindrance as polymers and readily interact with the structures shown in formulas (1) and (2) derived from polycarbonate diols constituting polycarbonate polyurethane, and are therefore preferred.
[0142] Urea carbamates are compounds obtained by forming carbamates from polyisocyanates and alcohols, and then further reacting them with polyisocyanates. Examples include compounds obtained by reacting a monohydric alcohol (such as 1-butanol) with dicyclohexylmethane-4,4'-diisocyanate, and monohydric alcohols (such as 1-butanol) with cyclohexane-1,2-dimethylbis(methylene) diisocyanate.
[0143] An adduct is an isocyanate with three or more functions obtained by reacting a polyisocyanate with a low-molecular-weight compound containing active hydrogen. Examples include compounds obtained by reacting trimethylolpropane with hexamethylene diisocyanate, compounds obtained by reacting trimethylolpropane with dicyclohexylmethane-4,4'-diisocyanate, and compounds obtained by reacting trimethylolpropane with cyclohexane-1,2-dimethylbis(methylene)diisocyanate.
[0144] By incorporating isocyanate-based crosslinking agents containing these urea-formate bodies, biuret bodies, or adducts into the coating composition, the reactivity is enhanced, crosslinking reactions are facilitated, the crosslinking density of the resulting coating layer can be increased, and the compactness of the resulting coating layer can be improved.
[0145] The preferred isocyanate-based crosslinking agent is a capped isocyanate-based crosslinking agent (C) that incorporates a capping agent to control the reactivity of the isocyanate. Examples of capping agents include: bisulfite compounds such as sodium bisulfite; pyrazole compounds such as 3,5-dimethylpyrazole, 3-methylpyrazole, 4-bromo-3,5-dimethylpyrazole, and 4-nitro-3,5-dimethylpyrazole; phenols such as phenol and cresol; aliphatic alcohols such as methanol and ethanol; active methylene compounds such as dimethyl malonate and acetylacetone; thiols such as butyl mercaptan and dodecyl mercaptan; amides such as acetanilide and acetamide; lactams such as ε-caprolactam and δ-valeractam; imides such as succinimide and maleimide; oximes such as acetaldehyde oxime, acetone oxime, and methyl ethyl ketone oxime; and amines such as diphenylaniline, aniline, and ethyleneimine. From a reactivity point of view, the preferred end-capping agent in this system is one with a pyrazole-based backbone.
[0146] Furthermore, for the purpose of improving the interaction with the resin used in combination, the above-mentioned end-capped isocyanate crosslinking agent (C) has a cyclohexane ring structure and / or a C5~C10 methylene chain structure in its molecule.
[0147] The content of the cyclohexane ring structure in the end-capped isocyanate-based crosslinking agent (C) is generally more preferably 10% by mass or more and 40% by mass or less, and more preferably 15% by mass or more and 35% by mass or less. By setting the content to 40% by mass or less, the mobility and flexibility of the crosslinking agent are easily ensured. By setting it to 10% by mass or more, the number of cyclohexane ring structure units that interact with the resin can be ensured, thus ensuring the strength of the resin in the coating layer and expecting an improvement in the particle retention force in the coating layer.
[0148] The content of the cyclohexane ring structure in the end-capped isocyanate crosslinking agent (C) is calculated based on the cyclohexane ring structure (-C6H). 10 The value is obtained by measuring the mass of -CH2- relative to 100g of the total mass of the end-capped isocyanate crosslinking agent (C). Specifically, it can be calculated from "the mole % and molecular weight of each component constituting the end-capped isocyanate crosslinking agent (C)," "the mole % of the components containing a cyclohexane ring among all components," and "the proportion of the molecular weight of the components containing a cyclohexane ring in the molecular weight."
[0149] The content of C5-C10 methylene chain structures in the end-capped isocyanate-based crosslinking agent (C) is generally more preferably 10% by mass or more and 40% by mass or less, and more preferably 15% by mass or more and 35% by mass or less. By setting the content to 40% by mass or less, it is easy to ensure the fluidity and flexibility of the resin. By setting it to 10% by mass or more, it is possible to ensure the number of units of the C5-C10 methylene chain structures that interact with the resin, thereby ensuring the strength of the resin in the coating layer and expecting an improvement in the particle retention force in the coating layer.
[0150] The content of C5-C10 methylene chain structures in the end-capped isocyanate crosslinking agent (C) is calculated by determining the C5-C10 methylene chain structure (-(CH2)). n The value obtained is the ratio of the mass of (-, n as above) to 100g of the total mass of the end-capped isocyanate crosslinking agent (C). Specifically, it can be calculated from "the molar percentage and molecular weight of each component constituting the end-capped isocyanate crosslinking agent (C)," "the molar percentage of the components having methylene chains with 5 or more carbon atoms and less than 10 carbon atoms among all components," and "the proportion of the molecular weight of the methylene chains with 5 or more carbon atoms and less than 10 carbon atoms among the molecular weights of the components having methylene chains with 5 or more carbon atoms and less than 10 carbon atoms."
[0151] The end-capped isocyanate-based crosslinking agent (C) may have a cyclohexane ring structure and / or a C5-C10 methylene chain structure in its molecule. Examples of diisocyanate components that can be used to prepare this end-capped isocyanate-based crosslinking agent (C) include pentamethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4-methylene dicyclohexyl diisocyanate, 1,2-bis(isocyanate methyl)cyclohexane, and 1,4-bis(isocyanate methyl)cyclohexane. Among these, isophorone diisocyanate, 4,4-methylene dicyclohexyl diisocyanate, 1,2-bis(isocyanate methyl)cyclohexane, and 1,4-bis(isocyanate methyl)cyclohexane are particularly preferred if at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group. Furthermore, hexamethylene diisocyanate and the like having a C5-C10 methylene chain structure are particularly preferred.
[0152] Furthermore, these isocyanate components can be used alone or in combination of two or more. There is no particular limitation on the ratio when combining two or more; it can be adjusted to obtain an isocyanate-based crosslinking agent that achieves the desired properties.
[0153] From the viewpoint of imparting water dispersibility in aqueous solvents, it is preferable to introduce hydrophilic groups into the end-capped isocyanate-based crosslinking agent (C). Furthermore, as hydrophilic groups, anionic groups such as carboxyl or sulfonic acid groups, and nonionic groups such as oxyalkyl groups are preferred. Crosslinking agents having these hydrophilic groups can be prepared by reacting a polyisocyanate, which serves as the base of the end-capped isocyanate-based crosslinking agent (C), with a compound having hydrophilic groups and reactive groups such as hydroxyl groups.
[0154] Therefore, the terminal isocyanate-based crosslinking agent (C) is preferably a terminal isocyanate-based crosslinking agent with 2 or more functions (more preferably 3 or more functions), and is a urea form, biuret form or adduct of a polyisocyanate compound.
[0155] When the total mass of the adhesive resin (especially polycarbonate polyurethane resin (A) and polyester resin (B)) and the end-capped isocyanate crosslinking agent (C) is set to 100% by mass, from the viewpoint of adhesion, the content of the adhesive resin is preferably 45-95% by mass, more preferably 55-90% by mass, further preferably 60-90% by mass, and most preferably 80-90% by mass. If it is 95% by mass or less, the strength of the coating film is maintained, and the adhesion under high temperature and high humidity is good. If it is 45% by mass or more, the flexibility of the coating layer is maintained, and the adhesion under normal temperature, high temperature and high humidity is maintained, which is preferred.
[0156] In addition, when the total mass of the adhesive resin and the crosslinking agent is set to 100% by mass, the content of the end-capped isocyanate crosslinking agent (C) is preferably 5 to 50% by mass, more preferably 10 to 45% by mass, even more preferably 10 to 40% by mass, and most preferably 10 to 20% by mass.
[0157] The present invention is characterized in that the polycarbonate polyurethane resin (A) used in the coating layer contains a cyclohexane ring structure and a C5-C10 methylene chain structure within its molecule, and the polyester resin (B) and the end-capped isocyanate crosslinking agent (C) each contain a cyclohexane ring structure and / or a C5-C10 methylene chain structure, thereby effectively exerting the effects of the present invention. The exact mechanism is not yet clear, but the coating layer of the present invention maintains the rigidity of the resin while also improving its flexibility, thus performing its function optimally as a coating layer. That is, the coating layer not only exhibits excellent adhesion to the substrate, such as the polyester film and functional layer, but also significantly improves adhesion over time. Therefore, a film that maintains its quality for a long period of time can be obtained.
[0158] (additive)
[0159] In the coating layer of the present invention, known additives may be added without impairing the effects of the present invention, such as surfactants, antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic slip agents, pigments, dyes, organic or inorganic particles, antistatic agents, nucleating agents, etc. However, it is preferable not to use substances that are environmentally unfriendly.
[0160] To further improve the anti-blocking properties of the coating layer, adding particles (especially inactive particles) to the coating layer is a preferred method. Examples of particles included in the coating layer include inorganic particles and organic polymer-based particles. Examples of inorganic particles include titanium dioxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, or mixtures thereof. Furthermore, they can be used in combination with other common inorganic particles, such as calcium phosphate, mica, lithium montmorillonite, zirconium oxide, tungsten oxide, lithium fluoride, and calcium fluoride. Examples of organic polymer-based particles include styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and organosilicon-based polymer-based particles.
[0161] The average particle size (average particle size based on the number of particles in SEM, the same below) of the particles (preferably inactive particles) in the coating layer is preferably 0.04 to 2.0 μm, more preferably 0.05 to 1.0 μm. When the average particle size of the inactive particles is 0.04 μm or more, it is easy to form unevenness on the surface of the coating layer, thus improving the operability of the easily bondable polyester film, such as its sliding and winding properties, and improving the processability during lamination, which is therefore preferred. On the other hand, when the average particle size of the inactive particles is 2.0 μm or less, particle shedding is less likely to occur, which is also preferred. The particle concentration in the coating layer is preferably 1 to 20% by mass relative to the resin composition.
[0162] (Formation of the coating layer)
[0163] In the coating layer forming composition (hereinafter also referred to as "coating liquid") used to form the coating layer, a surfactant may be further contained to improve the leveling properties during coating and to defoam the coating liquid. Examples of surfactants include cationic, anionic, and nonionic surfactants, with silicone-based, acetylenol-based, or fluorinated surfactants being preferred. These surfactants are preferably contained in the coating layer forming composition to the extent that they do not impair the suppression effect of iris spots under the three-wavelength LED light source or the degree of adhesion.
[0164] As a method for coating a coating liquid onto a polyester film, it can be applied to either the so-called online coating method, in which the coating is performed simultaneously during the polyester film making process, or the so-called offline coating method, in which the polyester substrate film is made and then coated separately using a coating machine. However, the online coating method is more efficient.
[0165] As a coating method, any known method can be used to coat the coating solution onto a polyethylene terephthalate (PET) film. Examples include reverse roller coating, gravure coating, kiss coating, die coating, roller brush coating, spray coating, air knife coating, wire rod coating, tube doctor blade coating, dip coating, and curtain coating. These methods can be used individually or in combination.
[0166] In this invention, a method for forming a coating layer on a polyester film can be described as applying a coating liquid containing a solvent, particles, and resin onto the polyester film and then drying it. As a solvent, water or a mixture of water and an organic solvent can be cited, but from an environmental perspective, water alone or a solvent composed of water and a water-soluble organic solvent is preferred. Examples of water-soluble organic solvents include alcohols such as isopropanol and ethanol; ketones such as methyl ethyl ketone; ethers such as butyl cellosolve; amines such as triethanolamine; and amides such as N-methylpyrrolidone.
[0167] The concentration of solid components in the coating liquid also depends on the type of binder resin, the type of solvent, etc., and is preferably 2% by mass or more, more preferably 4% by mass or more, relative to the total mass of the coating liquid. The concentration of solid components in the coating liquid is preferably 35% by mass or less, more preferably 15% by mass or less.
[0168] The drying temperature after coating depends on the type of adhesive resin, the type of solvent, the presence or absence of crosslinking agent, and the concentration of solid components. It is preferably above 80°C and more preferably below 250°C.
[0169] The coating amount of the coating solution can be adjusted to achieve a solid content on the dried polyester film, for example, 0.03~0.24 g / m². 2 Further, the concentration was 0.06~0.18 g / m³. 2 When a film stretching process is performed after coating and drying, the film can be prepared in such a way that the amount of solids on the stretched polyester film reaches the range described above.
[0170] The stretching process can be either uniaxial or biaxial stretching. The stretched polyester film can be heat-treated (e.g., 70~250°C, preferably 80~245°C) while fixed in a tenter frame, and then further relaxed at 120~250°C.
[0171] As described above, the easy-to-adhere polyester film of the present invention is manufactured through coating, drying, stretching and heat treatment processes.
[0172] The thickness of the coating layer can be 30 nm or more and 200 nm or less, 40 nm or more and 160 nm or less, etc. If it is prepared within this range, it is easy to balance processability and adhesion, therefore it is preferred. More preferably, it is 50 nm or more and 150 nm or less, and even more preferably, it is 70 nm or more and 110 nm or less. When the thickness of the coating layer is 30 nm or more, the adhesion becomes good and is preferred. When the thickness of the coating layer is 200 nm or less, adhesion is less likely to occur, which is also preferred.
[0173] Regarding the thickness of the coating layer, the cross-section of the cut film was observed using a transmission electron microscope (TEM), and the average value obtained by randomly measuring the thickness of the coating layer at 10 points was taken as the thickness of the coating layer.
[0174] laminated polyester film
[0175] This invention also provides a laminated polyester film in which functional layers with various properties are disposed on a coating layer of an easily adhesive polyester film. The functional layer refers to a layer with functions such as preventing reflection, suppressing glare, suppressing iris, and suppressing scratches, for example, a hard coating layer, an anti-glare layer, an anti-glare and anti-reflective layer, an anti-reflective layer, a low-reflection layer, and an antistatic layer. Various functional layers known in the art can be used for this functional layer, and there is no particular limitation on its type.
[0176] For example, when forming a hard coating layer on the coating layer, the material for the hard coating layer can be a known material without particular limitation. As such a material, a resin compound (especially a curable resin) that undergoes polymerization and / or reaction by drying, heat, chemical reaction, or irradiation with an electron beam, radiation, or ultraviolet light can be used. Examples of such curable resins include melamine-based, acrylic-based, silicone-based, and polyvinyl alcohol-based curable resins. From the perspective of obtaining high surface hardness or optical design, a photocurable acrylic-based curable resin is preferred. As such an acrylic-based curable resin, polyfunctional (meth)acrylate monomers and acrylate oligomers can be used. Examples of acrylate oligomers include polyester acrylates, epoxy acrylates, urethane acrylates, polyether acrylates, polybutadiene acrylates, and silicone acrylates. By mixing a reaction diluent, a photopolymerization initiator, a sensitizer, etc., into these acrylic-based curable resins, a coating composition for forming the aforementioned optical functional layer can be obtained.
[0177] The aforementioned hard coating can possess an anti-glare function that scatters external light. This anti-glare function is achieved by creating an uneven surface on the hard coating. Ideally, the haze of the film is 0-50%, more preferably 0-40%, and particularly preferably 0-30%. Of course, 0% is ideal, but it can be 0.2% or more, or even 0.5% or more.
[0178] Furthermore, by setting layers with different refractive indices as functional layers, low-reflection processing (anti-reflection processing) can be implemented by changing the light transmission characteristics, thereby suppressing light reflection. Ideally, the refractive index of functional layers such as hard coatings should be adjusted to a reflectance of 0 to 1.0%, more preferably 0 to 0.8%, and particularly preferably 0 to 0.5%. Of course, 0% is ideal, but it can be 0.05% or more, or 0.1% or more.
[0179] The easily bondable polyester film of the present invention can be used as a protective film for polarizers. Typically, a polarizer is formed by placing protective films on both sides of a polarizer, but the protective film on at least one side of the polarizer is preferably the easily bondable polyester film of the present invention. The protective film on the other side can be the easily bondable polyester film of the present invention, or it can be a non-birefringent film, such as a triacetyl cellulose film, an acrylic film, or a norbornene film.
[0180] Examples of polarizers include those containing dichroic materials such as iodine in a polyvinyl alcohol (PVA) film. The protective film is directly bonded to the polarizer or bonded via an adhesive layer, but bonding via an adhesive is preferred from the viewpoint of improving adhesion. In this case, the coating layer of the easily bondable polyester film of the present invention is preferably disposed on the surface of the polarizer or the surface of the adhesive layer. Examples of polarizers preferred for bonding the polyester film of the present invention include those obtained by dyeing / adsorbing iodine and dichroic materials onto a PVA film, uniaxially stretching it in a boric acid aqueous solution, and then washing / drying it while maintaining the stretched state. The stretching ratio of the uniaxial stretching is typically about 4 to 8 times. As a PVA film, PVA is preferred, and commercially available products such as "Kuraray Vinylon," "Tohcello Vinylon," and "Nichigo Vinylon" can be used. Examples of dichroic materials include iodine, diazo compounds, and polymethanone dyes.
[0181] Regarding the adhesive applied to the polarizer, when the adhesive layer is made thinner, an aqueous adhesive is preferred; that is, the adhesive components are preferably dissolved or dispersed in water. For example, polyvinyl alcohol resins, urethane resins, etc., are used as the main components. To improve adhesion, compositions incorporating isocyanate compounds, epoxy compounds, etc., can be used as needed. The thickness of the adhesive layer is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less.
[0182] When using polyvinyl alcohol-based resins as the main component of an adhesive, in addition to partially saponified polyvinyl alcohol and fully saponified polyvinyl alcohol, modified polyvinyl alcohol-based resins such as carboxyl-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, hydroxymethyl-modified polyvinyl alcohol, and amino-modified polyvinyl alcohol can also be used. The concentration of polyvinyl alcohol-based resin in the adhesive is preferably 1 to 10% by mass, more preferably 2 to 7% by mass.
[0183] For the adhesive applied to the polarizer, a photocurable adhesive is preferred to further improve productivity. The thickness of the cured adhesive layer can be arbitrarily set according to the characteristics of the polarizer; from the viewpoint of reducing adhesive material costs, a small thickness is preferred. Typically, it is 0.01 to 20 μm, preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm. When the adhesive layer thickness is 0.01 μm or more, air bubbles are less likely to be incorporated into the adhesive layer, resulting in good adhesion and durability, which is preferred. When the adhesive layer thickness is 20 μm or less, the adhesive reaction rate is sufficient, and the polarizer's resistance to damp heat becomes good, therefore, this is also preferred.
[0184] The photocurable adhesive is preferably composed of an epoxy compound that does not contain aromatic rings as the main component, and contains a photocationic curing component (I) and a photocationic polymerization initiator (II).
[0185] The photocatalytically curable component (I) is preferably composed primarily of an epoxy compound that does not contain aromatic rings. An epoxy compound that does not contain aromatic rings is an epoxy compound other than aromatic epoxy compounds, hereinafter referred to as an aliphatic epoxy compound. "Epoxy compound" refers to a compound having at least one epoxy group in its molecule. The aliphatic epoxy compound as the main component may contain two or more epoxy compounds. "Main component" means that the content of the aliphatic epoxy compound is 50% by mass or more in 100% by mass of the photocurable adhesive. The content of the aliphatic epoxy compound is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0186] Aliphatic epoxides can be epoxides with alicyclic rings or epoxides without alicyclic rings but consisting only of straight-chain hydrocarbon structures and / or branched hydrocarbon structures. Furthermore, aliphatic epoxides can contain unsaturated bonds such as double bonds, and may further contain heteroatoms (oxygen atoms, nitrogen atoms, sulfur atoms, halogen atoms, etc.) other than the oxygen atom contained in the epoxide group.
[0187] Photocationic polymerization initiator (II) can initiate cationic polymerization by irradiation with active energy rays, thereby curing the photocationic curable component (I) to form an adhesive layer. Photocationic polymerization initiator (II) generates cationic species or Lewis acids by irradiation with active energy rays such as visible light, ultraviolet light, X-rays, and electron beams, initiating the polymerization reaction of the photocationic curable component. Photocationic polymerization initiator (II) exerts its catalytic effect through light, therefore exhibiting excellent storage stability and workability even when mixed with the photocationic curable component.
[0188] Examples of photocationic polymerization initiators (II) include aromatic diazonium salts; aromatic iodonium salts, aromatic sulfonium salts, and iron-aromatic complexes.
[0189] Examples of aromatic diazonium salts include benzenediazohexafluoroantimonate, benzenediazohexafluorophosphate, and benzenediazohexafluoroborate.
[0190] Examples of aromatic iodonium salts include diphenyliodonium tetra(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate.
[0191] Examples of aromatic sulfonium salts include triphenylsulfonium hexafluorophosphate, triphenylsulfonium tetra(pentafluorophenyl)borate, 4,4-bis[diphenylsulfonyl]diphenylsulfide bis(hexafluorophosphate), 4,4-bis[bis(β-hydroxyethoxy)phenylsulfonium]diphenylsulfide bis(hexafluoroantimonate), 4,4-bis[bis(β-hydroxyethoxy)phenylsulfonium]diphenylsulfide bis(hexafluorophosphate), and 7-[bis(p-toluyl)sulfonyl]-2-iso Propylthioxanthone hexafluoroantimonate, 7-[bis(p-toluyl)sulfonyl]-2-isopropylthioxanthone tetra(pentafluorophenyl)borate, 4-phenylcarbonyl-4-diphenylsulfonyl-diphenyl sulfide hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4-diphenylsulfonyl-diphenyl sulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4-bis(p-toluyl)sulfonyl-diphenyl sulfide tetra(pentafluorophenyl)borate.
[0192] Examples of iron-aromatic complexes include xylene-cyclopentadienyl iron(II) hexafluoroantimonate, cumene-cyclopentadienyl iron(II) hexafluorophosphate, and xylene-cyclopentadienyl iron(II) tri(trifluoromethylsulfonyl)methane.
[0193] Photocationic polymerization initiator (II) can be used alone or in combination with two or more. Among the above, aromatic sulfonate salts in particular have ultraviolet absorption characteristics even in the wavelength region around 300 nm, thus exhibiting excellent curability and providing an adhesive layer with good mechanical and adhesive strength, and are therefore preferred.
[0194] The content of the photocationic polymerization initiator (II) is preferably 1 to 10 parts by mass relative to 100 parts by mass of the photocationic curable component (I), more preferably 2 to 6 parts by mass. By containing more than 1 part by mass of the photocationic polymerization initiator (II), the photocationic curable component (I) can be fully cured, and the obtained polarizing plate can be endowed with high mechanical strength and adhesive strength. On the other hand, if its content increases, the ionic substances in the cured product increase, thereby increasing the hygroscopicity of the cured product, which may reduce the durability of the polarizing plate. Therefore, the content of the photocationic polymerization initiator (II) is preferably 10 parts by mass or less relative to 100 parts by mass of the photocationic curable component (I).
[0195] The laminated polyester film of this invention is primarily used in the broader field of optical films, including base films for optical components such as LCDs, flat panel TVs, and CRTs, such as prism lenses, AR (anti-reflective) films, hard-coated films, diffuser plates, and shatterproof films; near-infrared absorbing filters for front panel components of plasma displays; and transparent conductive films such as touch panels and electroluminescent films. It can be suitably used in any application.
[0196] Examples of acrylic resins that are cured by electron beam or ultraviolet light to form the above-mentioned functional layers include compositions comprising oligomers of (meth)acrylates as reactive oligomers and (meth)acrylate-based monomers as reactive monomers (reactive diluents).
[0197] Examples of oligomers of (meth)acrylates include compounds with reactive (meth)acryloyl groups bonded to the backbone of (meth)acrylate resins, polyester acrylates, epoxy acrylates, polyurethane acrylates, silicone acrylates, melamine acrylates, polyether acrylates, etc.
[0198] Examples of (meth)acrylate monomers include monofunctional monomers such as ethyl (meth)acrylate and ethylhexyl (meth)acrylate; and polyfunctional monomers such as trimethylolpropane tri(meth)acrylate, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate.
[0199] As needed, a third component may be added, such as polyester resin, polyether resin, acrylic resin, epoxy resin, urethane resin, alkyd resin, spiroacetal resin, polybutadiene resin, polythiol polyene resin, polyol, etc., with a low molecular weight.
[0200] In the case of electron beam or ultraviolet-curable acrylic resins, acetophenones, benzophenones, Michaelis-Menten benzoylbenzoate, α-pentyl oxime ester, tetramethylthiuram monosulfide, and thioxanones can be used as photopolymerization initiators in the aforementioned resins. Furthermore, the photopolymerization initiator can be mixed with photosensitizers such as n-butylamine, triethylamine, and tri-n-butylphosphine.
[0201] Organosilicon (siloxane) thermosetting resins can be manufactured by hydrolyzing and condensing two or more organosilicon compounds, either alone or in combination, under acid or alkaline catalysts. Particularly in low-reflection applications, mixing one or more fluorosilane compounds and subjecting them to hydrolysis and condensation is preferred for improving low refractive index properties and stain resistance.
[0202] Manufacturing of laminated polyester films
[0203] By providing a functional layer on the coating layer of the easily adhesive polyester film of the present invention, a laminated polyester film can be manufactured. Specific methods will be described below, but are not limited to these. For example, the present invention can provide the following method: A method for manufacturing an easily adhesive polyester film, comprising a step of coating a coating layer forming composition on at least one side of a polyester film substrate.
[0204] The composition for forming the coating layer includes a polycarbonate polyurethane resin (A), a polyester resin (B), and a capped isocyanate crosslinking agent (C), and also includes particles.
[0205] The ingredients are as described in this instruction manual.
[0206] In one embodiment, the present invention provides a laminated polyester film having a functional layer on a coating layer of an easily adhesive polyester film.
[0207] A functional layer forming composition (coating liquid for forming a functional layer) is applied to the coating layer of the aforementioned easy-to-adhere polyester film. Examples of this functional layer forming composition include, for instance, the aforementioned electron beam or ultraviolet-curable acrylic resin (including its oligomers, monomers, etc.) or siloxane-based thermosetting resin. When the coating layer is applied to both sides of the easy-to-adhere polyester film, it can be applied to at least one coating layer. The functional layer forming coating liquid does not require special dilution, but dilution with an organic solvent is acceptable depending on the requirements of its viscosity, wettability, and film thickness. After applying the functional layer forming coating liquid to the film, the coating film is dried as needed, and then cured by electron beam or ultraviolet irradiation and heating according to its curing conditions, thereby forming a functional layer.
[0208] More typically, a coating liquid for forming a functional layer, as described above, can be used on a coating layer of an easily adhesive polyester film. The coating is applied using a wire rod or similar tool, and then dried, for example, at 60–100°C for 0.5–10 minutes to remove the solvent. Next, the film coated with the functional layer is irradiated with, for example, a high-pressure mercury lamp at 300 mJ / cm². 2 Ultraviolet light can be used to obtain laminated polyester films with functional layers.
[0209] In this invention, the thickness of the functional layer is preferably 1 to 15 μm. If the thickness of the functional layer is 1 μm or more, its effects on chemical resistance, scratch resistance, and stain resistance can be effectively exerted, and therefore it is preferred. On the other hand, if the thickness is 15 μm or less, the flexibility of the functional layer is maintained, and there is no concern about cracking, etc., and therefore it is preferred.
[0210] The easily bondable polyester film and laminated polyester film of the present invention are primarily suitable for optical applications, and therefore high transparency is preferred. Ideally, the lower limit of haze is 0%, and the closer to 0%, the better. The upper limit of haze is preferably 2%. If it is below 2%, light transmittance is good, and a clear image can be obtained in the liquid crystal display device, which is therefore preferred. Haze can be measured, for example, according to the method described in the embodiments described later.
[0211] (Evaluation of particle shedding properties)
[0212] For the easy-to-adhere polyester film of the present invention, in the particle shedding test, the amount of particles detached within the field of view is less than 30%. Since the amount of particles detached is less than 30%, the easy-to-adhere polyester film of the present invention can maintain a high degree of adhesion between the particles inside the coating layer and the resin, and can prevent the particles in the coating layer from detaching, thus preventing damage to the contact surface by the detached particles.
[0213] For example, the amount of particles detached can be 0.1% or more and 28% or less, 0.5% or more and 27% or less, or 1.0% or more and 26% or less.
[0214] By controlling the amount of particles to fall off within this range, damage to the contact surface from the falling particles can be prevented, while maintaining good sliding properties.
[0215] Here, the particle shedding test of the present invention can be performed by the method described later. By performing this method, particle shedding can be evaluated, taking into account friction and pressure on the surface in contact with the coating layer, during post-processing such as film formation and functional layer application, for example, when the film is rolled into a roll.
[0216] The damage to the polyester film and its opposite side can be evaluated using the methods described in the examples.
[0217] Specifically, for the friction fastness testing machine (Daiei Scientific Instruments Co., Ltd., RT-200), an easy-to-adhere polyester film is mounted with the easy-to-adhere layer facing upwards. A film with a low-reflection surface treatment is used at the contact point between the load head (2cm × 2cm, 200g) and the sample film. The film is refluxed 10 times at a distance of 10cm and a reciprocating speed of 2 seconds per cycle. The evaluation of this invention is that it generates friction under a constant load, for example, the effect of winding a film roll.
[0218] After the friction test, the obtained sample film was observed using a scanning electron microscope (magnification: 3000x). The number of particles X (particles) in the field of view was counted. Based on the number of particles Y (particles) in the same field of view before evaluation, the amount of detachment (%) was calculated by formula (1).
[0219] X / Y×100(%) …Equation (1)
[0220] For example, the difference in film haze (ΔHAZE) before and after the particle shedding test is less than 0.55%.
[0221] The difference in film haze can be, for example, 0.10% or more and 0.50% or less, 0.15% or more and 0.45% or less, and preferably 0.20% or more and 0.40% or less.
[0222] By keeping the haze difference of the film within such a range, damage to the contact surface by detached particles can be prevented, thereby maintaining good sliding properties and anti-adhesion properties.
[0223] Example
[0224] Next, the present invention will be described in detail using examples and comparative examples, but the present invention is not limited to the following examples, etc. Furthermore, the method for measuring the measured values used in the present invention is described below.
[0225] (1) Average particle size
[0226] [Method using scanning electron microscopy]
[0227] The average particle size of the particles present in the coating layer was determined by the following method. The particles were photographed using a scanning electron microscope (SEM), and the maximum diameter (distance between the two farthest points) of 300 to 500 particles was measured at a magnification of 2 to 5 mm for the smallest particle size. The arithmetic mean of these particles was taken as the average particle size.
[0228] Dynamic light scattering method
[0229] The average particle size was determined during particle manufacturing and film fabrication using dynamic light scattering. The sol was diluted with a dispersion medium, and the parameters of the dispersion medium were measured using a submicron particle analyzer N4 PLUS (Beckman Coulter). The average particle size was calculated using the cumulative moment method. The average particle size in the sol was observed using dynamic light scattering; if particle aggregation was present, the average particle size of these aggregated particles was also observed.
[0230] (2) Haze of optically bondable polyester film
[0231] The haze of the easy-to-adhere polyester film was measured using a turbidimeter (Nippon Denshoku, NDH2000) according to JIS K 7136:2000.
[0232] (3) Haze of polyester film before and after damage assessment
[0233] The difference in film haze (ΔHAZE) before and after the particle shedding test is calculated by the following formula (2).
[0234] ΔHAZE=A(%)-B(%)…(2)
[0235] A (%): Film haze before particle shedding test
[0236] B (%): Film haze after particle shedding test
[0237] (Evaluation of particle shedding properties)
[0238] For the friction fastness tester (Daei Scientific Instruments Manufacturing Co., Ltd., RT-200), the easy-to-adhere polyester film is installed with the easy-to-adhere layer facing upwards. A film with a low-reflection surface treatment is used at the contact part between the load head (2cm×2cm, 200g) and the sample film. The film is rubbed 10 times at a distance of 10cm and a speed of 2 seconds per rub.
[0239] After the friction test, the obtained film was observed using a scanning electron microscope (magnification: 3000x). The number of particles X (particles) in the field of view was counted. Based on the number of particles Y (particles) in the same field of view before evaluation, the amount of detachment (%) was calculated using formula (1).
[0240] X / Y×100(%) …Equation (1)
[0241] (Evaluation of damage)
[0242] Using an optical microscope (50x), the thin film with low-reflection surface processing obtained during the evaluation of particle shedding was observed, and the damage was determined as follows.
[0243] ◎: The number of damaged segments after the particle shedding test is less than 2.
[0244] 〇: The number of damaged segments after the particle shedding test is more than 2 but less than 5.
[0245] △: The number of damaged segments after the particle shedding test is 5 or more but less than 8.
[0246] ×: The number of damage lines after the particle shedding test is 8 or more.
[0247] The damage here refers to the number of damages with a length of 10 mm or more in the reciprocating direction of the load head.
[0248] (Anti-adhesion evaluation)
[0249] Cut the sample into two 10cm x 5cm squares, overlap them with their respective evaluation surfaces, and apply a 1kg / cm² pressure to the center of each side. 2 After the load was placed in an oven at 50°C for 24 hours, two samples were peeled off, and the peeling condition was judged according to the following evaluation criteria. Five tests were conducted on one sample.
[0250] ◎: There is no sound during peeling, and no peeling marks are left.
[0251] 0: It makes a slight sound when peeling off, but leaves no trace.
[0252] △: Makes a sound during peeling, leaving traces on part or the entire surface.
[0253] ×: Not stripped
[0254] (4) Specific viscosity ηsp / c (unit: dl / g)
[0255] 0.10 g of polyester resin was dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4), and the viscosity was measured using an Ubbelohde viscometer at 30 °C.
[0256] (5) Observation using a cross-section of a transmission electron microscope
[0257] After cutting easily bondable polyester film into 1mm × 10mm pieces and embedding them in epoxy resin, thin sections parallel to the short side of the embedded sample were prepared using an ultramicrotome. Next, the sections were stained with ruthenium tetroxide. For areas without significant damage, observation was performed using a transmission electron microscope (JEM2100, NEC) at an accelerating voltage of 200kV and magnification of 20,000x. Based on the observed images of the coating layer, the thickness of the coating layer was measured at 10 points at each level, and the average value was taken as the coating layer thickness.
[0258] (6) Resin composition of polyester
[0259] Polyester resin was dissolved in deuterated chloroform, and the analysis was performed using a Varian GEMINI-200 nuclear magnetic resonance (NMR) analyzer. 1 H-NMR analysis was used to determine the mole percentage of each component based on its integral ratio.
[0260] (7) Viscosity of polyester resin dispersion
[0261] Add the aqueous dispersion of polyester resin to a 140cc glass bottle, and measure the viscosity of the aqueous dispersion using a ModelBL (TOKIMEC INC.) viscometer with a rotor of 60 rpm for 1 minute in a constant temperature bath at 25°C.
[0262] [Polycarbonate polyurethane resin]
[0263] Synthesis of polycarbonate polyurethane resin (PCPU-1):
[0264] 28.0 parts by mass of 4,4'-diphenylmethane diisocyanate, 63.6 parts by mass of polycarbonate diol with a melting point of 33°C and a main raw material of 1,4-butanediol / 1,6-hexanediol (75 / 25 molar ratio) with a number average molecular weight of 1000, 7 parts by mass of dimethylolpropionic acid, and 200 parts by mass of methyl ethyl ketone as solvent were added to a four-necked flask equipped with a stirrer, a serpentine condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer. The mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere. The infrared spectrum of the reaction solution was measured to confirm the disappearance of isocyanate groups in the reaction solution. Then, after cooling the solution to room temperature, 8.2 parts by mass of triethylamine were added to obtain a polycarbonate polyurethane resin (PCPU-1) solution with a solid content of 50.0% by mass.
[0265] The polycarbonate polyurethane resin (PCPU-1) has an overall cyclohexane ring structure content of 0.0% by mass and a methylene chain structure with 5 or more carbon atoms and less than 10 carbon atoms content of 11.3% by mass.
[0266] Preparation of an aqueous dispersion of polycarbonate polyurethane resin (PCPU-1) (PCPU-1WD):
[0267] Add the specified amount of water to a reaction vessel equipped with a high-speed homogenizer, adjust the temperature to 25°C, and stir at a speed of 2000 min... -1 The polycarbonate polyurethane resin (PCPU-1) solution was slowly added while stirring and mixing to achieve aqueous dispersion. Then, methyl ethyl ketone, used as a solvent, was removed under reduced pressure. The concentration was adjusted by water to prepare an aqueous dispersion (PCPU-1WD) of polycarbonate polyurethane resin (PCPU-1) with a solid content of 35.0% by mass.
[0268] Synthesis of polycarbonate polyurethane resin (PCPU-2) and preparation of its aqueous dispersion (PCPU-2WD):
[0269] Instead of 1,4-butanediol / 1,6-hexanediol (=75 / 25 (molar ratio)), the main raw material for polycarbonate diol was changed to 1,4-cyclohexanediol / 1,6-hexanediol (=75 / 25 (molar ratio)). Otherwise, PCPU-2 was prepared in the same manner as PCPU-1, and an aqueous dispersion (PCPU-2WD) was obtained in the same manner as PCPU-1WD. The overall cyclohexane ring structure of this polycarbonate polyurethane resin (PCPU-2) was 29.1% by mass, and the proportion (content) of methylene chain structures with 5 or more but less than 10 carbon atoms was 8.5% by mass.
[0270] [Polyester resin]
[0271] Manufacturing of polyester resin (PEs-1):
[0272] Polyester resin (PEs-1) was polymerized according to a known polymerization method. The composition of the resulting polymer was then analyzed. 1 ¹H-NMR analysis was performed, and the molar percentage of each component was determined by its integral ratio. The results are recorded in Table 1. The specific viscosity of the obtained polyester resin was 0.583 dl / g.
[0273] The following describes the abbreviations recorded in Table 1.
[0274] TPA: Terephthalic acid
[0275] IPA: Isophthalic acid
[0276] CHMM: Cyclohexylmethylmalonic acid
[0277] DSS: Sodium dimethyl isophthalate-5-sulfonate
[0278] EG: Ethylene glycol
[0279] HD: 1,6-Hexanediol
[0280] DEG: Diethylene glycol
[0281] NPG: Neopentyl Glycol
[0282] CHDM: 1,4-Cyclohexanediethanol
[0283] Here, the proportion (content) of the cyclohexane ring structure of the polyester (PEs-1) is 12.6% by mass, and the proportion (content) of the methylene chain structure with 5 or more carbons and less than 10 carbons is 0.0% by mass.
[0284] Preparation of polyester aqueous dispersion (PEs-1WD):
[0285] In a reactor equipped with a stirrer, thermometer, and reflux device, 30 parts by weight of copolyester resin (PEs-1) and 15 parts by weight of ethylene glycol-n-butyl ether were added. The mixture was heated and stirred at 110°C to dissolve the resin. After the resin was completely dissolved, 55 parts by weight of water were slowly added to the polyester solution while stirring. After the water was added, the liquid was cooled to room temperature while stirring to prepare a milky white aqueous dispersion of polyester resin (PEs-1) (PEs-1WD) with a solid content of 25.1% by weight. The viscosity of the obtained aqueous dispersion was 84 mPa·s.
[0286] Manufacturing of polyester resin (PEs-2) and preparation of polyester aqueous dispersion (PEs-2WD):
[0287] Polyester resin (PEs-2) was produced using a known polymerization method, similar to the polymerization of the polyester resin (PEs-1) described above. The composition ratio was determined in the same manner as for PEs-1, and the specific viscosity of the resulting resin was evaluated. The results are recorded in Table 1.
[0288] Here, the proportion (content) of the cyclohexane ring structure of the polyester (PEs-2) is 12.8% by mass, and the proportion (content) of the methylene chain structure with 5 or more carbons and less than 10 carbons is 0.0% by mass.
[0289] A polyester aqueous dispersion (PEs-2WD) was prepared in the same manner as the preparation of the polyester aqueous dispersion (PEs-1WD). As with PEs-1WD, the solids concentration and liquid viscosity were evaluated. The results are recorded in Table 2.
[0290] [Table 1]
[0291]
[0292] [Table 2]
[0293]
[0294] [Polyisocyanate compounds]
[0295] Polyisocyanate compound (PI-1):
[0296] Referring to Japanese Patent Application Publication No. 8-225511, a polyisocyanate compound (PI-1) having a biuret structure was prepared using dicyclohexylmethane-4,4'-diisocyanate. The NCO concentration of this polyisocyanate compound was 16.0 wt%. Furthermore, the proportion (content) of the cyclohexane ring structure was 37.0 wt%, and the proportion (content) of the methylene chain structure with 5 or more but less than 10 carbon atoms was 0.0 wt%.
[0297] Polyisocyanate compound (PI-2):
[0298] Using cyclohexane-1,2-dimethylbis(methylene) diisocyanate instead of dicyclohexylmethane-4,4'-diisocyanate, a polyisocyanate compound (PI-2) having a biuret structure was prepared in the same manner as polyisocyanate compound (PI-1). The NCO concentration of this polyisocyanate compound was 21.6 wt%. Furthermore, the proportion (content) of the cyclohexane ring structure was 50.0% by mass, and the proportion (content) of the methylene chain structure with 5 or more but less than 10 carbon atoms was 0.0% by mass.
[0299] [Cross-linking agent]
[0300] Preparation of an aqueous dispersion (C-1WD) of a capped isocyanate-based crosslinking agent (C-1):
[0301] 140.1 parts by mass of a polyisocyanate compound (PI-1) with a biuret structure, based on dicyclohexylmethane-4,4'-diisocyanate, 50.0 parts by mass of dipropylene glycol dimethyl ether, and 53.9 parts by mass of 3,5-dimethylpyrazole were added to a flask equipped with a stirrer, thermometer, and reflux condenser. The mixture was stirred at 70°C under a nitrogen atmosphere for 2 hours. The infrared spectrum of the reaction solution was then measured to confirm the disappearance of the isocyanate group absorption. Next, after cooling to room temperature, 6 parts by mass of polyethylene glycol (n=12) monolaurate were added, and the mixture was stirred at 2000 min... -1 Water was added while stirring and mixing. The concentration was adjusted by water to prepare an aqueous dispersion (C-1WD) of 30.0% by mass of the end-capped isocyanate crosslinking agent (C-1).
[0302] Here, the proportion (content) of the cyclohexane ring structure in the solid component of the end-capped isocyanate crosslinking agent (C-1) is 26.7% by mass, and the proportion (content) of the methylene chain structure with 5 or more carbon atoms and less than 10 carbon atoms is 0 by mass.
[0303] Preparation of an aqueous dispersion (C-2WD) of a capped isocyanate-based crosslinking agent (C-2):
[0304] Similarly to the preparation of the aqueous dispersion (C-1WD), an aqueous dispersion (C-2WD) of the end-capped isocyanate crosslinking agent (C-2) was prepared using a polyisocyanate compound (PI-2) and a polyisocyanate adduct (PI-4).
[0305] The solid component of the end-capped isocyanate crosslinking agent (C-2) has a cyclohexane ring structure with a mass ratio of 32.9% and a methylene chain structure with 5 or more carbon atoms and less than 10 carbon atoms with a mass ratio of 0%.
[0306] [Example 1]
[0307] (Preparation of coating solution)
[0308] Prepare a coating solution with the following composition.
[0309] 43.47 parts by weight of water
[0310] 30.57 parts by weight of isopropanol
[0311] Silica sol A-1 4.15 parts by weight
[0312] (Silica sol with an average particle size of 100 nm and a solid content concentration of 4.0% by mass)
[0313] PCPU-1WD 5.42 parts by weight
[0314] (Solid component concentration is 35.0% by mass)
[0315] PEs-1WD 7.58 parts by weight
[0316] (The concentration of solid components is 25.1% by mass)
[0317] C-1WD 8.43 parts by weight
[0318] (Solid component concentration is 30.0% by mass)
[0319] 0.05 parts by weight of surfactant
[0320] (Organosilicon-based, solid content concentration 10.0% by mass)
[0321] 0.34 parts by weight of high-boiling-point solvent
[0322] (Manufacturing of easy-to-adhere polyester film)
[0323] As a polymer raw material for films, PET resin granules with an intrinsic viscosity (solvent: phenol / tetrachloroethane = 60 / 40) of 0.62 dl / g and substantially free of particles were dried at 135°C for 6 hours under reduced pressure of 133 Pa. The dried granules were then fed to an extruder and melt-extruded into sheets at approximately 280°C. These sheets were then rapidly cooled and solidified on rotating cooling metal rollers with a surface temperature maintained at 20°C to obtain unstretched PET sheets.
[0324] Next, the coating solution was applied to one side of the PET film using a roller coating method and then dried at 80°C, resulting in a final coating weight of 0.12 g / m² after stretching and drying. 2 The film was then adjusted in the following manner. Next, it was stretched to 4.0 times its original length in the width direction using a tenter frame at 150°C. With the length in the width direction of the film fixed, it was heated to 230°C and then further relaxed in the width direction at 230°C to obtain an easy-to-adhere polyester film with a thickness of 50μm.
[0325] The thickness of the adhesive coating layer of the obtained adhesive polyester film is 102 nm, and the film haze is 0.66%.
[0326] The particle shedding property of the obtained easy-to-adhere polyester film was evaluated, and the shedding rate was 12%.
[0327] [Examples 2-3, 5-7]
[0328] By changing the polycarbonate polyurethane resin, polyester resin, crosslinking agent, and particles used to the combinations listed in Table 3, an easy-to-adhere polyester film was obtained in the same manner as in Example 1.
[0329] The obtained easily bondable polyester film was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 3.
[0330] [Examples 4, 9, 10, 14, 15]
[0331] The polycarbonate polyurethane resin, polyester resin, and crosslinking agent used were changed to the combinations listed in Table 3. Regarding the particles, in addition to using silica sol A-1, silica sol A-2 (average particle size of 80 nm, solid content concentration of 40.0% by mass) or silica sol A-3 (average particle size of 50 nm, solid content concentration of 40.0% by mass) was also used. Otherwise, the operation was the same as in Example 1 to obtain an easy-to-adhere polyester film.
[0332] The resulting easily bondable polyester film was evaluated in the same manner as in Example 1, and then the process was repeated as in Example 1 to obtain a laminated polyester film with a functional layer. The various evaluation results are shown in Table 3.
[0333] [Examples 8, 11-12]
[0334] The polycarbonate polyurethane resin, polyester resin, and crosslinking agent used were changed to the combinations listed in Table 3. The particles were changed to silica sol A-4 (average particle size of 450 nm, solid content concentration of 4.0% by mass), silica sol B (average particle size of 50 nm, solid content concentration of 3.5% by mass), or particles C (average particle size of 300 nm, solid content concentration of 20% by mass) instead of silica sol A-1. Otherwise, the same procedure as in Example 1 was followed to obtain an easy-to-adhere polyester film.
[0335] The resulting easily bondable polyester film was evaluated in the same manner as in Example 1, and then the process was repeated as in Example 1 to obtain a laminated polyester film with a functional layer. The various evaluation results are shown in Table 3.
[0336] [Example 13]
[0337] The polycarbonate polyurethane resin, polyester resin, and crosslinking agent used were changed to the combinations listed in Table 3. Regarding the particles, in addition to using silica sol A-1, particles D (average particle size of 45 nm and solid content of 13% by mass) were also used. Otherwise, the same procedure as in Example 1 was followed to obtain an easy-to-adhere polyester film.
[0338] The resulting easily bondable polyester film was evaluated in the same manner as in Example 1, and then the process was repeated as in Example 1 to obtain a laminated polyester film with a functional layer. The various evaluation results are shown in Table 3.
[0339] [Comparative Example 1]
[0340] (Preparation of coating solution)
[0341] Prepare a coating solution with the following composition, and operate in the same manner as in Example 1 to obtain an easily bondable polyester film.
[0342] 47.63 parts by weight of water
[0343] 33.28 parts by weight of isopropanol
[0344] Silica sol A-1 4.52 parts by weight
[0345] (Silica sol with an average particle size of 100 nm and a solid content concentration of 4.0% by mass)
[0346] PCPU-2WD 5.90 parts by weight
[0347] (Solid component concentration is 35.0% by mass)
[0348] PEs-1WD 8.25 parts by weight
[0349] (The concentration of solid components is 25.1% by mass)
[0350] 0.05 parts by weight of surfactant
[0351] (Organosilicon-based, solid content concentration 10.0% by mass)
[0352] 0.37 parts by weight of high-boiling-point solvent
[0353] The resulting easily bondable polyester film was evaluated in the same manner as in Example 1, and then the process was repeated as in Example 1 to obtain a laminated polyester film with a functional layer. The various evaluation results are shown in Table 3.
[0354] [Comparative Example 2]
[0355] The polycarbonate polyurethane resin, crosslinking agent, and particles used were changed to the combination listed in Table 3, and an equal amount of polyvinyl alcohol (manufactured by Kuraray Co., Ltd.) was used instead of polyester resin. Otherwise, the same procedure as in Example 1 was followed to obtain an easy-to-adhere polyester film.
[0356] The resulting easily bondable polyester film was evaluated in the same manner as in Example 1, and then the process was repeated as in Example 1 to obtain a laminated polyester film with a functional layer. The various evaluation results are shown in Table 3.
[0357] [Compare Examples 3 and 4]
[0358] The polycarbonate polyurethane resin listed in Table 3 was removed, and the polyester resin listed in Table 3 was replaced with an amount correspondingly increased to the amount of polycarbonate polyurethane resin removed. Otherwise, the same procedure as in Example 1 was followed to obtain an easy-to-adhere polyester film.
[0359] The resulting easily bondable polyester film was evaluated in the same manner as in Example 1, and then the process was repeated as in Example 1 to obtain a laminated polyester film with a functional layer. The various evaluation results are shown in Table 3.
[0360] [Table 3]
[0361]
[0362] The easily bondable polyester film of the present invention, by improving the flexibility of the coating layer and maintaining high adhesion to lubricant particles, can prevent the particles in the coating layer from falling off and prevent damage to the contact surface from the falling particles. Therefore, during post-processing such as film formation and functional layer application of the film having the coating layer, damage to the opposite side in contact with the coating layer can be suppressed during winding, and damage to the functional layer formed on the opposite side can also be suppressed. In addition, since it also has excellent anti-blocking and transparency, it can be widely used in optical applications and the like.
[0363] On the other hand, since Comparative Example 1 does not contain a capped isocyanate crosslinking agent (C), damage occurs on the opposite side of the coating layer, and damage also occurs on the functional layer formed on the opposite side.
[0364] Comparative Example 2 does not contain polyester resin (B), therefore the opposite side of the coating layer is damaged, and the functional layer formed on the opposite side is also damaged.
[0365] Comparative Examples 3 and 4 do not contain polycarbonate polyurethane resin (A), therefore the opposite side of the coating layer is damaged, and the functional layer formed on the opposite side is also damaged.
[0366] Industrial availability
[0367] The easily bondable polyester film of the present invention improves the flexibility of the coating layer and maintains high adhesion to lubricant particles, thereby preventing particle detachment from the coating layer and preventing damage to the contact surface from detached particles. Furthermore, it also exhibits excellent anti-blocking properties and transparency. Therefore, it can be widely used in optical applications and the like.
Claims
1. An easy-to-adhere polyester film, comprising an easy-to-adhere polyester film having a polyester film substrate and a coating layer, The coating layer is formed from a composition comprising polycarbonate polyurethane resin (A), polyester resin (B), end-capped isocyanate crosslinking agent (C), and particles. In the particle shedding test, the amount of particles shed within the field of view is less than 30%.
2. The easily bondable polyester film according to claim 1, wherein, The difference in film haze before and after the particle shedding test is less than 0.55%.
3. The easily bondable polyester film according to claim 1, wherein, The polycarbonate polyurethane resin (A) has the structure shown in formula (1) in its molecule. In the formula, * represents the bonding site, and n represents an integer from 5 to 10.
4. The easily bondable polyester film according to claim 1, wherein, The polyester resin (B) is a polyester resin having the structure shown in formula (1) in its molecule. In the formula, * represents the bonding site, and n represents an integer from 5 to 10.
5. A method for manufacturing an easy-to-adhere polyester film, comprising the method of manufacturing the easy-to-adhere polyester film according to any one of claims 1 to 4, comprising: The process of coating a composition for forming a coating layer onto at least one side of a polyester film substrate. The composition for forming the coating layer comprises polycarbonate polyurethane resin (A), polyester resin (B), end-capped isocyanate crosslinking agent (C), and particles. The polycarbonate polyurethane resin (A) has the structure shown in formula (1) in its molecule. In the formula, * represents the bonding sites, and n represents an integer from 5 to 10. The polyester resin (B) has the structure shown in formula (1) in its molecule. In the formula, * represents the bonding sites, and n represents an integer from 5 to 10. The terminated isocyanate-based crosslinking agent (C) has the structure shown in formula (1) in its molecule. In the formula, * represents the bonding site, and n represents an integer from 5 to 10.
6. A laminated polyester film, wherein a functional layer is further provided on the coating layer of the easy-to-adhere polyester film of claim 1.
7. A method for manufacturing a laminated polyester film, comprising the method for manufacturing the laminated polyester film of claim 6, comprising: The process of coating a functional layer forming composition onto the coating layer of the easily adhesive polyester film according to any one of claims 1 to 4.
Citation Information
Patent Citations
Production of polyisocyanate containing biuret
JP1996225511A
Easily-adhesive optical polyester film
JP2011168053A
Laminated polyester film
JP2011246663A
Laminated polyester film
JP2013063610A